Characterization of DPP-4 and α-amylase inhibitors from Melicope glabra (Blume) T.G.Hartley and Melicope latifolia (DC.) T.G.Hartley (Rutaceae) for type 2 diabetes therapy - Quek, Alexandra (2021)
Melicope glabra and Melicope latifolia are plants of Rutaceae family that can be found locally in Malaysia. To date, scientific reports on the phytochemicals and bioactivities of the two species are still limited, especially on antidiabetic activity. In this research, the potential antidiabetic properties and bioactive components of M. glabra and M. latifolia were investigated. Assay-guided isolation of phytoconstituents on M. glabra gave five compounds which were p-geranyl coumaric acid (49), stigmasterol (56), scopoletin (64), evolitrine (12), and pachypodol (68). Notably, p-geranyl coumaric acid (49) and evolitrine (12) were isolated for the first time from the species M. glabra. Meanwhile, four compounds were isolated from M. latifolia namely β-sitosterol (55), halfordin (88), methyl p-coumarate (89), and protocatechuic acid (90). Halfordin (88), methyl p-coumarate (89), and protocatechuic acid (90) were reported from the species M. latifolia for the first time. The chloroform extract from M. glabra leaves showed the highest inhibition activities with the IC50 values of 169.40 ± 9.30 and 303.64 ± 10.10 μg/mL against dipeptidyl peptidase-4 (DPP-4) and α-amylase, respectively. Among the compounds, the highest DPP-4 inhibition was presented by scopoletin (64) followed by pachypodol (68) with respective IC50 values of 36.34 ± 2.80 and 66.34 ± 2.30 μM. Meanwhile, halfordin (88) from M. latifolia was the most potent α-amylase inhibitor with an IC50 value of 195.27 ± 4.41 μM followed by stigmasterol (56) which exhibited an IC50 value of 304.02 ± 16.20 μM. This was supported by in silico docking analysis which revealed that scopoletin (64) exhibited the strongest binding (binding affinity of -7.3 kcal/mol) and showed the highest number of interactions with the amino acids that were critical for DPP-4 inhibition such as Ser630, Arg125, Tyr662, Tyr666, and Glu205 while halfordin (88) presented the highest number of interactions with critical amino acids of α-amylase such as His305, Thr163, Asp300, Trp59, Tyr62, and Trp58 with the binding affinity of -6.6 kcal/mol. Meanwhile, the strongest binding towards α-amylase was showed by stigmasterol (56) (binding affinity of -10.2 kcal/mol) which mainly formed hydrophobic interactions with the amino acids at the binding site. The in silico findings in combination with in vitro activities suggested scopoletin (64), pachypodol (68), halfordin (88), and stigmasterol (56) as potential antidiabetic agents. The in vivo antidiabetic investigation of M. glabra chloroform leaves extract revealed that the dose of 200 mg/kg showed a more pronounced antidiabetic effect as compared to the lower doses of 50 and 100 mg/kg by lowering the blood glucose level in diabetic rats by 25.63%. The increment in glucagon-like peptide-1 (GLP-1) and insulin levels observed in the treated diabetic rats could be attributed to the DPP-4 inhibition property of the M. glabra extract as shown in the in vitro analysis. In conclusion, this study exhibited the potential of M. glabra and M. latifolia as the sources of antidiabetic alternatives or as natural therapies for the management of Type 2 diabetes mellitus.